2020
DOI: 10.3390/ijerph17186936
|View full text |Cite
|
Sign up to set email alerts
|

Are Advanced Glycation End Products in Skin Associated with Vascular Dysfunction Markers? A Meta-Analysis

Abstract: Evidence exists regarding the association between advanced glycation end products and different cardiovascular disease subclinical processes, such as arterial stiffness and atherosclerosis. With this systematic review and meta-analysis, we aimed to provide a synthesis of the evidence regarding the association of arterial stiffness measured by pulse wave velocity and atherosclerosis measured by carotid intima media thickness with skin autofluorescence. A systematic search was performed using: MEDLINE (PubMed), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 53 publications
(78 reference statements)
1
9
0
Order By: Relevance
“…Moreover, several skin proteins fluorescence within wavelengths overlap with AGEs spectra, thus SAF measurement is not specific [44]. However, investigators have established that AGE reader measures tissue AGE that is highly positively correlated with fluorescent and nonfluorescent tissue AGE measures in skin biopsies [51].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several skin proteins fluorescence within wavelengths overlap with AGEs spectra, thus SAF measurement is not specific [44]. However, investigators have established that AGE reader measures tissue AGE that is highly positively correlated with fluorescent and nonfluorescent tissue AGE measures in skin biopsies [51].…”
Section: Discussionmentioning
confidence: 99%
“…Lutgers et al demonstrated that SAF provides additional information to the UKPDS risk score for the estimation of cardiovascular prognosis in T2D [ 71 ]. In addition, there is emerging evidence indicating that SAF is an important biomarker not only of the presence of cardiovascular disease but also of their outcomes [ 72 , 73 ].…”
Section: Saf and Diabetic Macrovascular Complicationsmentioning
confidence: 99%
“…AGE accumulation leads to quantitative and qualitative alterations of collagens and elastin, which could contribute to the decreased elastic properties of the vessels, thereby playing a role in arterial stiffness [ 87 ]. SAF is strongly correlated with pulse wave velocity, brachial and aortic augmentation indices, and ankle-brachial index, all of them markers of arterial stiffness [ 72 ]. Birukov et al [ 84 ] recently investigated the relationships between SAF and vascular stiffness in a large study performed in diabetic and non-diabetic populations.…”
Section: Saf and Diabetic Macrovascular Complicationsmentioning
confidence: 99%
“…A systematic review and meta-analysis by Saz-Lara, A. et al [ 53 ], aimed to provide a synthesis of the evidence regarding the association of arterial stiffness measured by pulse wave velocity and atherosclerosis measured by carotid intima media thickness with advanced glycation end products assessed by skin autofluorescence. An innovative approach to indirectly estimate vascular subclinical damage.…”
Section: What Is New In Prevention and Treatment Of Cardiovascular Di...mentioning
confidence: 99%